Cytomegalovirus resistance in transplant patients Review - David Tarragó (Global Journal of Clinical Virology - Peertechz Publications, 2023)
CMV is a major cause of disease and mortality in patients undergoing Solid Organ Transplants (SOT) and Hematopoietic Stem Cell Transplants (HSCT). In SOT, CMV infection usually establishes itself in the first three months after transplantation in patients who do not receive prophylaxis.